Effect of maternal hydration on the increase of amniotic fluid index - Borges, Vera Therezinha Medeiros [UNESP]; Rososchansky, J. [UNESP]; Abbade, Joelcio Francisco [UNESP]; Dias, Adriano [UNESP]; Peraçoli, José Carlos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2011)
The objective of this study was to determine the effect of maternal hydration with oral isotonic solution and water on the amniotic fluid (AF) index of women with normohydramnios. Women with a normal AF index and gestational age between 33 and 36 weeks without maternal complications were randomized into three groups [isotonic solution (Gatorade (R)), water, control]. The isotonic solution and water groups were instructed to drink 1.5 L of the respective solution and the control group was instructed to drink 200 mL water over a period of 2 to 4 h. AF index was measured before and after hydration by Doppler ultrasonography. The investigator performing the AF index measurement was blind to the subject's group. Ninety-nine women completed the study without any adverse maternal effects. The median increase in AF index after hydration was significantly greater for the isotonic solution and water groups than for the control group. There was no significant difference between the isotonic solution and water groups. Hydration with isotonic solution and water caused a 10-fold (95% CI: 2.09-49.89) and 6-fold (95% CI: 1.16-30.95) increase in the chance of a 20% increase of AF index, respectively. Maternal hydration with isotonic solution or water increased the AF index in women with normohydramnios.
Keywords: Amniotic fluid index; Maternal oral hydration; Isotonic solution